Environmental and low temperature geochemistry - Ryan, Peter Crowley (Wiley Blackwell / Washington D. C, 2014)
Environmental and Low-Temperature Geochemistry presentsconceptual and quantitative principles of geochemistry in order tofoster understanding of natural processes at and near theearth's surface, as well as anthropogenic impacts on the natural environment. It provides the reader with theessentials of concentration, speciation and reactivity of elementsin soils, waters, sediments and air, drawing attention to boththermodynamic and kinetic controls. Specific featuresinclude:* An introductory chapter that reviews basic chemical lprinciples applied to environmental and low-temperature geochemistry